Parametric design of scaled-down pressurised thermal shock test specimens using inelastic analysis. (1st May 2017) - Coules, H.E.; Orrock, P.J.; Truman, C.E.
Graphical abstract: Highlights: Thermal shock tests for nuclear reactor pressure vessels can be miniaturised. Models show that scaled-down tests can give equivalent fracture initiation conditions. Specimens equivalent to the NESC-1 thermal shock test have been designed. Abstract: Pressurised thermal shock tests that simulate fracture conditions relevant to nuclear reactor pressure vessels are difficult to perform and require very large specimens. This study examines the feasibility of scaled-down specimens to allow easier testing. A series of finite element models was used to design scaled-down specimens that produce a crack-driving force, crack tip temperature trajectory and constraint conditions very similar to those which occurred in a previous large-scale spinning cylinder experiment known as NESC-1. It is shown that equivalent conditions can be achieved in much smaller specimens than NESC-1 using a practical set of testing parameters.